IMPLEMENTATION OF THE PROGRAM POLICY TO ACCELERATE STUNTING REDUCTION - Pratidina, Ginung; Yuniar, Putri Gina; Wahyudin, Cecep; Rahmawati, Rita; Iskandar, Abu Bakar; Apriliyani, Neng Virly; Firliandoko, Robby; Lyndon, Novel Anak; Sastrawan, Berry (Universitas Djuanda, 2025)
This research discusses how the policy of Presidential Decree Number 72 of 2021 concerning the Acceleration of Stunting Reduction is implemented with a research focus at the UPTD Cicurug Health Center, Cicurug District, Sukabumi Regency, which aims to find out whether the policy is implemented well and whether there are success factors or inhibiting factors in the process of implementing the policy. The method used in this research is a descriptive quantitative method. Meanwhile, the sampling technique used was purposive sampling technique and disproportionate random sampling technique by determining the sample size using the Slovin formula which then resulted in a total of 117 respondents. Measurement of policy implementation variables is carried out using a Likert scale with a questionnaire instrument, the results of which are then processed using the weight mean score (WMS) formula. The results of the recapitulation of questionnaire calculations with operationalization of variables based on the Kapioru Policy Implementation theory (2014) obtained an average score of 4.23 with a very good assessment category. This shows that the implementation of the stunting reduction acceleration program policy at the Cicurug Community Health Center UPTD, Cicurug District, Sukabumi Regency has been implemented very well, although there are still several indicators that need to be improved. The novelty of this research is in terms of the theory used and the research results which show that there is a special strategy from the implementing institution which is one of the factors in the success of implementing the policy.